GENESIS AND EXHUMATION DYNAMICS OF ECLOGITES IN THE KOKCHETAV MASSIF NEAR MOUNT SULU-TYUBE, KAZAKHSTAN - Perchuk A.L.; Yapaskiirt V.O.; Podlesskii S.K. (My University, 1998)
Exhumation velocity and cooling rates were calculated for eclogites from the megamelange zone near Mount Sulu-Tyube in the Kokchetav Massif, Kazakhstan. The calculations were based on the reconstruction of the thermodynamic parameters of eclogite metamorphism during decompression and on modeling of the diffusion-controlled homogenization of a garnet grain with unusual growth zoning. The garnet is distinguished for strong compositional discontinuities between its outermost rim and euhedral core. Paragenetic analysis indicates that a garnet rim of distinct composition has developed around a garnet porphyroblast with the transition from the epidote amphibolite to eclogite metamorphic facies. A notable feature of the garnet is that its early core did not participate in the reaction and, thus, retained its euhedral habit. Our calculations indicate that the sharp boundaries between the garnet growth zones could be preserved after the growth stage only if the average exhumation velocity of the rock and its cooling rate were very high: 62 mm/year and 318°C/m.y., respectively.